Gut microbiota-metabolome crosstalk in allergic diseases: mechanistic insights and translational opportunities - Qin, HanBin; Sui, Jiaxin; Wang, Shuang; Lv, Xiaojing; Zhang, Zile; Lin, Xinhua; Liu, Xuexia; Zhang, Hua (Frontiers in Allergy, 2025)
The gut microbiota and its metabolites play important roles in the pathogenesis of various diseases. The diversity of the gut microbiota is closely related to the development and function of the human immune system. Dysbiosis, characterized by alterations in the species, quantity, and distribution of microbial community, may disrupt immune tolerance mechanisms, thereby inducing excessive immune responses to allergens and increasing the risk of allergic diseases. Various metabolites, such as short-chain fatty acids (SCFAs), bile acids, and amino acid metabolites, exert significant regulatory effects on the development of allergic diseases by modulating immune cell function, maintaining intestinal barrier integrity, and participating in signal transduction pathways. A comprehensive investigation into the relationship between allergic diseases and gut microbiota and their metabolites not only aids in elucidating the pathogenesis of allergic diseases but also provides novel insights and a theoretical foundation for developing innovative diagnostic methods, preventive strategies, and therapeutic options. This article systematically reviews the latest findings regarding the mutual influence between gut microbiota and the metabolome in host immune regulation, as well as the impact of this interaction on the development of allergic diseases, aiming to offering new strategies for the prevention and treatment of allergic diseases.